2022
DOI: 10.3390/biom12081158
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Role of RNA m6A Modification in Glial Cells in the Regulation of Neurological Diseases

Abstract: Glial cells are the most abundant and widely distributed cells that maintain cerebral homeostasis in the central nervous system. They mainly include microglia, astrocytes, and the oligodendrocyte lineage cells. Moreover, glial cells may induce pathological changes, such as inflammatory responses, demyelination, and disruption of the blood–brain barrier, to regulate the occurrence and development of neurological diseases through various molecular mechanisms. Furthermore, RNA m6A modifications are involved in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Furthermore, we find that the role of METTL3 in nerve cells varies from neuronal stem cells to neurons to the pro-inflammatory phenotype of microglia to astrocytes. However, to our knowledge and in our previously published review [ 73 ], there have been few studies on the roles of METTL3 in oligodendrocytes and the anti-inflammatory phenotype of microglia. As anti-inflammatory phenotype microglia possess similar functions to those of macrophages and studies have indicated the important roles of METTL3 in regulating the activation of macrophages [ 74 ], we predict that METTL3 will be relevant in regulating anti-inflammatory phenotype microglia activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we find that the role of METTL3 in nerve cells varies from neuronal stem cells to neurons to the pro-inflammatory phenotype of microglia to astrocytes. However, to our knowledge and in our previously published review [ 73 ], there have been few studies on the roles of METTL3 in oligodendrocytes and the anti-inflammatory phenotype of microglia. As anti-inflammatory phenotype microglia possess similar functions to those of macrophages and studies have indicated the important roles of METTL3 in regulating the activation of macrophages [ 74 ], we predict that METTL3 will be relevant in regulating anti-inflammatory phenotype microglia activation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in gene expression or phenotype occurrence may be attributed to epigenetic modifications, such as the prevalent N 6 methyladenosine (m 6 A) modification of RNA molecules, which has received increasing attention in the investigation of the mechanism of biological processes. 4,5 RNA m 6 A is one of the most prominent epigenetic modification, and is associated with three regulatory factors: writers, erasers and readers. 4,5 Writers are commonly known for the activity of methyltransferases to add methyl groups (-CH 3 ), whereas erasers are primarily demethylases with the opposite ability, to remove -CH 3 , and readers primarily recognize m 6 A RNA and decide the fate of RNA.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…4,5 RNA m 6 A is one of the most prominent epigenetic modification, and is associated with three regulatory factors: writers, erasers and readers. 4,5 Writers are commonly known for the activity of methyltransferases to add methyl groups (-CH 3 ), whereas erasers are primarily demethylases with the opposite ability, to remove -CH 3 , and readers primarily recognize m 6 A RNA and decide the fate of RNA. 4,5 Writers, also called m 6 A methyltransferase complex, consists of a multicomponent that is primarily installed by methyltransferase-like 3 (METTL3) and methyltransferase-like 14 (METTL14), as well as some other regulatory subunits such as the Wilms' tumour 1 (WT1) associated protein (WTAP).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Glial cells are the most abundant cells and induce several changes in pathological conditions such as inflammation, demyelination and disruption of BBB ( You et al, 2022 ). RNA m6A modification is observed to regulate microglia’s inflammatory processes ( Zhang F. et al, 2022 ).…”
Section: Effect Of Rna M6a Methylationmentioning
confidence: 99%